Electrochemical detection of Cu(ii) using amino-functionalized MgFe2O4/Reduced graphene oxide composite. Issue 17 (20th April 2018) - Xu, Juncui; Li, Zhenyu; Yue, Xianming; Xie, Fazhi; Xiong, Shiquan
Abstract : An amino-functionalized MgFe2 O4 /reduced graphene oxide (rGO) was prepared by the combination of MgFe2 O4 /rGO and 1, 6-hexanediamine, and employed for the electrochemical detection of Cu(ii ) ions. Abstract : In this study, an amino-functionalized MgFe2 O4 /reduced graphene oxide (rGO) composite was prepared by the combination of MgFe2 O4 /rGO and 1, 6-hexanediamine (HDA) and employed for the electrochemical detection of Cu(ii ) ions. The composite was obtained through a one-pot method, and it was characterized by SEM, XRD, FT-IR and electrochemical methods. Some important parameters such as pH of solution, amount of modification, deposition time, and deposition potential were optimized. The determination of Cu(ii ) ions was performed using HDA/rGO/MgFe2 O4, rGO/MgFe2 O4 and MgFe2 O4 via square-wave anodic stripping voltammetry. The lowest detection limit obtained was 0.2 nM, and the sensitivity was 0.0172 μA nM −1 . The proposed electrode was also used for the detection of Cu(ii ) ions in soil sample. Overall, the proposed method could provide a reference for the detection of metal ions.